A tour of India in one workplace: investigating complex and gendered relations in IT. Issue 2 (3rd April 2018) - Dhar-Bhattacharjee, Sunrita; Richardson, Helen
Abstract : Purpose: The purpose of this paper is to investigate the situation of women working as information technology (IT) professionals in different regions of India within multi-national enterprises (MNEs). The research is part of a cross-national study that compared gendered relations in the UK and Indian IT sectors. The complex roles that region, class and caste and gendered values and norms have in shaping women's work and lives in India are discussed. Design/methodology/approach: The cross-national research assumed common themes as part of a programme of in-depth interviewing and observations during site visits. The "safari method" was adopted with research conducted by a sole fieldworker with intimate knowledge of the languages and cultures of both India and the UK. The research considered intersectionality and difference and aimed to understand material structures and cultural meanings evident from the research process. Findings: There are significant differences in organisational culture even within MNEs sharing common legislative and policy environments. The IT sector in India offers opportunities for middle- and upper-class women professionals and the cultural – including identity – barriers to working in technical areas often experienced in western countries are not replicated in India. Nevertheless, this has not meant any significant improvements in gendered relations at work and in the Indian society. There are also particular influences of regional, class and caste differences manifested in IT workplaces, contributing to inequality. Originality/value: This paper adds to the understanding of the situation of women in IT sector including within MNEs giving insights into the workings of global capitalist enterprises. The research offers appreciation of the complexity of social differences and whether opening up opportunities for women professionals in India can contribute to the inclusive growth or will maintain the current patterns of inequality.